Transformasi Pengetahuan dalam QS. Al-Baqarah Ayat 260: Analisis Tematik atas Peran Burung Sebagai Media Epistemik - Afrizal El Adzim Syahputra; Alhadi Zaenal Abidin; M. Triono Al Fata (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2025)
This article analyzes the process of knowledge transformation in Qur’an Surah Al-Baqarah (2):260 by positioning birds as an epistemic medium in faith-based learning. The study aims to explain how revelation, empirical observation, and direct experience interact in enhancing the quality of Prophet Ibrahim’s (peace be upon him) conviction. The research employs a thematic (mawḍū‘ī) tafsir method with a qualitative approach, utilizing linguistic analysis of the verse, comparative examination of classical and contemporary Qur’anic exegesis, and the framework of Islamic epistemology. The findings indicate that the event described in this verse represents stages of knowledge transformation from ‘ilm al-yaqīn to ‘ayn al-yaqīn, culminating in ḥaqq al-yaqīn through an empirical demonstration directly commanded by Allah. Birds function as concrete media that enable experiential validation of the truth of revelation. These findings affirm that the Qur’an does not merely present theological doctrine but also offers an experiential learning model that is highly relevant to the development of epistemology and educational methodology in contemporary Islamic education. This study underscores the importance of an empirical approach in faith education that maintains a balance between rationality and spirituality.